Investigation on galvanic corrosion behaviors of CFRPs and aluminum alloys systems for automotive applications. Issue 6 (27th December 2018) - Wu, Xiayu; Sun, Jiakun; Wang, Jiaming; Jiang, Yiming; Li, Jin
Abstract : Carbon fiber reinforced plastics (CFRP) are promising lightweight materials for vehicle applications while there is a concern of galvanic corrosion when carbon fiber composite materials are connected with other metals. The galvanic corrosion behaviors were studied between CFRP and aluminum alloys in this paper. Several techniques were applied including potentiodynamic polarization test (PPT), galvanic corrosion current test (GCT), and immersion test (IT). It yielded that there existed obvious galvanic corrosion between CFRP and aluminum alloys. Additionally, influences of different surface conditions, carbon fiber concentrations, and substrate materials on the galvanic corrosion behavior were compared and discussed. Carbon fiber concentrations determine the conductivity of the CFRPs, that will have an impact on the corrosion behaviors. The exposure of the carbon fiber attributed to the polishing process will increase the corrosion rate, which confirms the importance of the elongation and hydroscopicity of the carbon fibers. Abstract : Carbon fiber composites and aluminum alloys have been selected to be coupled and studied for galvanic corrosion behavior using different techniques. Influences of different surface conditions, carbon fiber concentrations, and substrate materials on the galvanic corrosion behaviors were compared.